THÁI ĐỘ CỦA GIÁO VIÊN VÀ SINH VIÊN CHÍNH QUY NĂM NHẤT KHOA SƯ PHẠM TIẾNG ANH - TRƯỜNG ĐẠI HỌC NGOẠI NGỮ VỀ PHƯƠNG PHÁP HỌC CỘNG TÁC TRONG DẠY VÀ HỌC NGOẠI NGỮ - Đan, Thị Thúy Anh (2020)
The radical demand for foreign language competent users, specifically English has created a need for Asian countries to innovate their traditional teaching approaches and upgrade learners’ communicative competency. In Vietnam, such movement as the National Foreign Language 2020 Project has been in progress, in the hope that people can use another tongue independently as a second language. This has consequently led to the widespread adoption of several Western-based English language teaching approaches, and cooperative learning is a case in point. Regarding the potential benefits of CL for the students’ language acquisition, this study was carried out to explore the attitudes of teachers and students of FELTE, ULIS towards this approach, hence better understand the perceived effectiveness and level of motivation gained from cooperative learning. The results of this paper were quite encouraging, and they might challenge several notions about the inappropriateness of CL in Vietnamese context, and ULIS in particular. Specifically, teachers and first year students of FELTE, ULIS generally showed favorable attitudes and agreed about the level of effectiveness and motivation derived from certain aspects of CL, yet there are several differences in the perceptions of these two groups.